Geochemical evidence on the depositional environment of Nummulites accumulations around Elazig, Sivas, and Eskisehir (Turkey) in the middle Eocene sub-epoch - Sinanoglu, Derya; Sasmaz, Ahmet (Springer Heidelberg, 2019)
The main objective of this study was to investigate the major, trace, and rare earth element (REEs) contents, in order to reconstruct the physico-chemical parameters of the marine paleoenvironment which hosted the investigated Nummulites accumulations. The studied samples were collected from Kirkgecit Formation-Elazig, Mamuca Formation, and Bogazkoy Formation in Ipresian-Lutetian ages. All Nummulites samples for major oxides, trace, and rare earth elements were analyzed by using inductively coupled plasma atomic emission spectroscopy (ICP-MS). The CaO contents in Nummulites range from 52.52 to 54.41 wt%. The (Tb/Yb)(n)-(La/Yb)(n) ratios of Nummulites show that all rare earth element (REE) contents were depleted during the sedimentation. The PAAS-normalized REE patterns of the Nummulites show similar trends that indicate a weak decrease to heavy REEs from light REEs. All Nummulites have negative Ce and positive Eu anomalies. The Y/Ho values vary between 28 and 41, and these values are close to that of sea water and carbonate rocks. Our findings show that Nummulites had several physicochemical features such as increases in fO(2) and pH or decrease in temperature in the shallow marine environment.
Keywords: Nummulites; Limestone; Trace element content; REE geochemistry; Turkey